The Changing Financial and Policy Role of State Governments Regarding Higher Education and Prospects for the Future - Daniel T. Layzell (Educational Considerations, 2003)
Higher education in the United States grew rapidly in the post-World War II era, more than doubling the total number of degree-granting institutions (1,851 to 4,084) and increasing the total number of students enrolled more than five-fold (2.7 million to 14.8 million) between 1950 and 2000.